Liquid pump-enabled hydrogen refueling system for heavy duty fuel cell vehicles: Fuel cell bus refueling demonstration at Stark Area Regional Transit Authority (SARTA). (11th November 2021) - Li, Jimmy; Youn, Edward; Ramteke, Ashwin; McRobie, Jordan; Hansen, Erik; Hall, Cullen; Kratschmar, Kenneth; Prakash, Alvin; Conrad, Kirt; Ku, Anthony Y.
Abstract: We have demonstrated a hydrogen (H2 ) refueling solution capable of delivering precooled, compressed gaseous hydrogen for heavy duty vehicle (HDV) refueling applications by refueling transit buses over a three-month period under real-world conditions. The system uses a submerged pump to deliver pressurized liquid H2 from a cryogenic storage tank to a dispensing control loop that vaporizes the liquid and adjusts the pressure and temperature of the resulting gas to enable refueling at 35 MPa and temperatures as low as −40 °C, consistent with the SAE J2601 standard. Using our full-scale mobile refueler, we completed 118 individual bus filling events using 13 different vehicles, involving a total of 3, 700 kg of H2 dispensed. We report filling statistics from the entire campaign, details on individual fills (including fill times, final state of charge, benefits of pre-cooled fills, and back-to-back filling capabilities), and discuss transit agency feedback on technology performance. In our final test, the system successfully completed an endurance test using a single dispenser involving 52 consecutive individual fills over an 11.5-h period, dispensing 1, 322 kg of H2 with an average fill rate of 3.4 kg/min and peak rate of 7.1 kg/min, and reaching an average SOC of 97.6% across all fills. Graphical abstract: Image 1 Highlights: A liquid H2 pump-enabled solution for 35 MPa H2 refueling has been demonstrated. Thirteen different in-service transit vehicles were refueled over a 3 month period. 118 individual vehicle fills, 3, 700 kg H2 total, average final state of charge >96%. Endurance test: 1, 322 kg; 52 fills; average fill rate 3.4 kg/min; 97.6% SOC.